Linking Phytoplankton Variability to Atmospheric Blocking in an Eastern Boundary Upwelling System. Issue 6 (29th May 2022) - Le, Chengfeng; Wu, Ming; Sun, Hongwei; Long, Shang‐min; Beck, Marcus W.
Abstract: The oceanic ecosystems in the eastern boundary upwelling systems (EBUS) are expected to be influenced by climate change, but specific mechanisms describing their connections are not well understood. Using a 20‐year time‐series record of satellite and climate data, we identified a strong linkage between phytoplankton variability in a EBUS and a high latitude, large‐scale atmospheric process. The winter–spring phytoplankton variability in the Canary Current Upwelling System was associated to the atmospheric blocking events over Greenland. These Greenland blocking events were primarily caused by the persistence of quasi‐stationary, large‐scale high atmosphere pressure fields. These fields forced the eddy‐driven jet stream to shift south, which caused a weakening of the equatorward alongshore winds over the upwelling system. As a result, the wind‐driven upwelling was suppressed, and phytoplankton growth was inhibited. These results identified a previously unknown source driving interannual phytoplankton variability in the EBUS, underscoring the importance of contributions of atmospheric connections on the coastal upwelling ecosystems. Plain Language Summary: Eastern boundary upwelling systems (EBUS) represent several of the most productive ecosystems in the world. Climate change is expected to profoundly affect ecosystems in these systems. However, the physical process connects climate change and EBUS ecosystems is not fully understood. The Canary upwelling system is one of the four EBUS in North Atlantic. It supports the highest primary production among the four upwelling systems, and contributes largely to global fisheries catch. However, what climate factors and how they modulate ecosystem variability in this coastal upwelling system remains unclear. In this study, by using a time‐series of satellite observations and reanalysis climate data, we show that the winter–spring phytoplankton bloom variability in the coastal upwelling system is strongly influenced by large‐scale atmospheric circulation such as Greenland blocking. The mechanism is associated with blocking forced jet stream shifting. This finding identifies a previously unknown source for interannual variability in the subtropical North Atlantic coastal upwelling system. It also underscores the importance of monitor not only local conditions but also teleconnections to understand present and future climate change impacts on coastal upwelling systems. Key Points: A unknown climatic driver in physical and biological variability in an eastern boundary upwelling systems was identified The connection between Greenland blocking and Canary phytoplankton was established A conceptual model to explain the mechanism of the teleconnection was proposed